1970
DOI: 10.1139/g70-044
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Chromosome Number and Structure in Plant Cells Grown in Suspension Cultures

Abstract: Cell suspension cultures of Triticum monococcum, Triticiam aestivum, Glycine max, Melilotus alba, and Haplopappus gracilis, were examined to determine whether chromosomal changes had occurred during culture. All cultures except H. gracilis showed change in chromosome number and the two species of Triticum showed abnormal karyotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…The phenomenon of polyploidization in haploid and diploid cells accompanying repetition of subculture has been demonstrated in cultures of several plant species by many workers (Bennici et al 1968;Kao et al 1970;Sacristan 1971;Collins et al 1972;Bayliss 1973Bayliss ,1975bSingh et al 1975;Matthews and Vasil 1976). Demoise and Partanen (1969) demonstrated that with repetition of subculture of calli derived from embryos of Paeonia sufruticosa, the fall in frequency of diploid cells was accompanied by the emergence of tetraploid and octoploid cells.…”
Section: Discussionmentioning
confidence: 97%
“…The phenomenon of polyploidization in haploid and diploid cells accompanying repetition of subculture has been demonstrated in cultures of several plant species by many workers (Bennici et al 1968;Kao et al 1970;Sacristan 1971;Collins et al 1972;Bayliss 1973Bayliss ,1975bSingh et al 1975;Matthews and Vasil 1976). Demoise and Partanen (1969) demonstrated that with repetition of subculture of calli derived from embryos of Paeonia sufruticosa, the fall in frequency of diploid cells was accompanied by the emergence of tetraploid and octoploid cells.…”
Section: Discussionmentioning
confidence: 97%
“…Structural changes of chromosomes are often produced in cultured cells : These are dicentric chromosome (Norstog et al 1969;Kao et al 1970 ;Singh et al 1972 ;Bayliss 1975;Orton 1980), acentric fragment (Norstog et al 1969 ;Kao et al 1970;Singh et al 1972), translocation (Sacristan andWendt-Gallitelli 1971, 1973), and deletion of a chromosome segment (the present work). These changes reported in cultured cells were reviewed by Sunderland (1977).…”
Section: Discussionmentioning
confidence: 79%
“…The :3',. with 14 chromosomes leading to their predominance in the population, as suggested by Kao et al, (1970). The two tetraploid lines also differed in stability.…”
Section: Discussionmentioning
confidence: 98%